Can a small change in the tilapia’s on-going feeding strategy impair its growth? - doi: 10.4025/actascianimsci.v35i3.18290 - Caldini, Nayara Nunes; Pereira, Nayagra Vidal; Rebouças, Vanessa Tomaz; Sá, Marcelo Vinícius do Carmo e (Acta Scientiarum. Animal Sciences, 2013)
The aim of the present work was to answer the following question: can a small change in the tilapia’s on-going feeding strategy impair its growth? In the initial phase of the study, fish were evenly distributed and maintained for two weeks in four tanks. In tanks 1 and 2, the ration was given in three equal meals at 8, 12 and 16h or at 9, 13 and 17h, respectively. In tanks 3 and 4, there was only one daily meal at 9 or 10 o’clock, respectively. In the second 8-week phase, fish from tank 1 were distributed into two groups in ten 100-L tanks: the 8-12-16 group, in which fish were always fed at 8, 12 and 16h; and the 8-12-16/9-13-17 group, in which fish were fed at 8, 12 and 16h in the first four weeks and at 9, 13 and 17h in the last four weeks. Fish from tank 2 were allocated into five 100-L tanks and their mealtimes were maintained unchanged. The same procedures were used in tanks 3 and 4. The delay of one hour in the allowance of the artificial diet has significantly reduced fish survival.